Protection of personal non-property rights of persons in the armed conflict: ukrainian realities and international experience - Kovalchuk, Alla (ScienceRise: Juridical Science, 2022)
The problem of protection of personal rights and human freedoms during armed conflicts is raised. Particular attention is paid to ensuring Protocol I to the Geneva Convention, which states that the parties to any armed conflict must distinguish between civilians and the military and direct their actions only against military objectives. Civilians should be provided with living conditions, as far as possible, and should be protected from murder, violence, stress, repression, destruction of their property and hostage-taking. Their personal rights, honor, dignity and personal integrity must be respected and guaranteed. The aggressor state does not comply with international law, and the Ukrainian security system, in turn, has identified gaps in the organization of rapid evacuation of civilians. As a result, a significant number of citizens remained on the territory of hostilities and were forced to provide themselves with at least a minimum of personal security. Accordingly, it is necessary to study the experience of other countries of the world that have suffered armed aggression in their territories in the context of positive practices of protection of the population, forced to find themselves in the territory of hostilities. The article draws conclusions about the formation of a new security policy and the development of preventive measures to protect the personal rights and freedoms of citizens during armed conflicts